2003
DOI: 10.1105/tpc.012849
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis NPR1 Disease Resistance Protein Is a Novel Cofactor That Confers Redox Regulation of DNA Binding Activity to the Basic Domain/Leucine Zipper Transcription Factor TGA1

Abstract: The Arabidopsis NPR1 protein is essential for regulating salicylic acid-dependent gene expression during systemic acquired resistance. NPR1 interacts differentially with members of the TGA class of basic domain/Leu zipper transcription factors and regulates their DNA binding activity. Here, we report that although TGA1 does not interact with NPR1 in yeast two-hybrid assays, treatment with salicylic acid induces the interaction between these proteins in Arabidopsis leaves. This phenomenon is correlated with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
405
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(413 citation statements)
references
References 64 publications
6
405
1
1
Order By: Relevance
“…Of the four Cys residues in TGA1 (Cys-172, Cys-260, Cys-266, and Cys-287), Cys-260, Cys-266, and Cys-287 are located in the first Gln-rich domain. Cys-260 and Cys-266 were previously shown to form an intramolecular disulfide bridge under oxidative conditions, which is reduced in a redox-dependent manner (Després et al, 2003). Most recently, additional complex posttranslational modifications have been reported for TGA1 Cys residues, including the formation of an intramolecular disulfide bridge between Cys-172 and Cys-287 and S-nitrosylation or S-glutathionylation of Cys-260 and Cys-266 (Lindermayr et al, 2010).…”
Section: Roxy1 Might Affect Pan Protein Activities By Posttranslationmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the four Cys residues in TGA1 (Cys-172, Cys-260, Cys-266, and Cys-287), Cys-260, Cys-266, and Cys-287 are located in the first Gln-rich domain. Cys-260 and Cys-266 were previously shown to form an intramolecular disulfide bridge under oxidative conditions, which is reduced in a redox-dependent manner (Després et al, 2003). Most recently, additional complex posttranslational modifications have been reported for TGA1 Cys residues, including the formation of an intramolecular disulfide bridge between Cys-172 and Cys-287 and S-nitrosylation or S-glutathionylation of Cys-260 and Cys-266 (Lindermayr et al, 2010).…”
Section: Roxy1 Might Affect Pan Protein Activities By Posttranslationmentioning
confidence: 99%
“…Upon pathogen infection and salicylic acid accumulation, NONEXPRESSOR OF PR GENES1 (NPR1) is translocated from the cytoplasm into the nucleus and interacts with TGA transcription factors. The NPR1/TGA1 protein interaction depends on the reduced state of two Cys residues in TGA1, as an intramolecular disulfide bridge formed between Cys-260 and Cys-266 prevents this interaction (Després et al, 2003). Salicylic acid-induced ROXY19 interacts with several TGA transcription factors and negatively modulates jasmonic acid-responsive PDF1.2 transcription in Arabidopsis, suggesting that this GRX is involved in the reduction of TGA1 (Ndamukong et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Once SA accumulates upon pathogen attack and alters the cellular redox state, this provokes a reduction of the disulphide bonds in the NPR1 protein by the thioredoxins TRX-h3 and TRX-h5 (Tada et al, 2008). Even further, a change in the oxidation state of cysteine residues of TGA transcription factors has been shown to be necessary to promote their interaction with NPR1 in the nucleus (Després et al, 2003). The reduced form of the NPR1 oligomer releases NPR1 monomers that translocate to the nucleus and interact with the oxidised TGA transcription factors, promoting the induction of defence response genes (Tada et al, 2008).…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…TGA1 and TGA4 did not bind to NPR1 in yeast assays. However, by using an in planta transient expression assay mechanistically similar to the yeast two-hybrid system, Després and co-workers demonstrated that TGA1 does interact with NPR1 in Arabidopsis leaves upon SA treatment (Després et al, 2003). In the same study, yeast two-hybrid assays with chimeric TGA1 proteins in which various domains were exchanged with TGA2 revealed that a 30 amino acid segment is important for NPR1 interaction.…”
Section: Tga Function and Redox Regulationmentioning
confidence: 95%